Development of an E-worksheet Based on Problem-Based Learning with Prompting Question Technique on Chemical Equilibrium Material - Amanda, Putry; Syolendra, Dwi Finna (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Students' misunderstandings and low level of active involvement in learning chemical equilibrium and the incomplete application of problem-based learning models. This study was motivated by students' misconceptions and low active involvement in learning chemical equilibrium material. In addition, the implementation of the problem-based learning model has not been fully realized, and students still experience difficulties in connecting and applying chemical concepts to everyday life. The purpose of this study is to develop a problem-based learning e-worksheet with prompting question techniques on chemical equilibrium material that is valid and practical. The method used is research and development (R&D) with the Plomp model, which includes the preliminary research and prototyping phases. Validity analysis techniques were analyzed using Aiken's V scale, and practicality analysis techniques were analyzed using a percentage formula. The validity analysis yielded an average score of 0.925, which is considered valid. The practicality test results showed that the e-worksheet is highly practical, with an average score of 94.375% from teachers and 89.38% from students. Based on the results of the study, it can be concluded that the development of an e-worksheet based on problem-based learning with prompting question techniques on chemical equilibrium material is valid and very practical.